Indonesia Lokalitas Budaya Sasak pada Film Perempuan Sasak Terkahir - Indah Rosita Lana; Saharudin Saharudin; Ahmad Sirulhaq (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
The research question addressed in this study is how Sasak cultural locality and cultural elements are portrayed in the film Permpuan Sasak Terakhir. This study aims to uncover the Sasak cultural locality and cultural elements contained in the film Permpuan Sasak Terakhir by Sandi Amaq Rinjani. The research design employed in this study is qualitative descriptive research, with data sourced from the film Permpuan Sasak Terakhir Data collection was conducted using the observation method, followed by note-taking. The results of this study indicate the presence of distinct Sasak cultural locality and cultural elements. These include cultural locality, knowledge system locality, artistic locality, and technological system locality. Keywords: Locality, Sasak Culture, Permpuan Sasak Terakhir